Survival outcomes of adjuvant radiotherapy and chemotherapy in women with stage I serous papillary and clear cell carcinoma of the endometrium: a Korean multicenter study - Kim, Miseon; Kwon, Byung Su; Chang, Ha Kyun; Lee, Seungmee; Chang, Suk-Joon; Choi, Jin Young; Park, Sang-Yoon; Lee, Maria; Ryu, Hee-Sug; Kim, Yong Beom (Journal of gynecologic oncology, 2019)
To compare the survival outcomes of adjuvant radiotherapy and chemotherapy in women with uterine-confined endometrial cancer with uterine papillary serous carcinoma (UPSC) or clear cell carcinoma (CCC). Medical records of 80 women who underwent surgical staging for endometrial cancer were retrospectively reviewed. Stage I UPSC and CCC were pathologically confirmed after surgery. Survival outcomes were compared between the adjuvant radiotherapy and chemotherapy groups. Fifty-four (67.5%) and 26 (32.5%) women had UPSC and CCC, respectively. Adjuvant therapy was administered to 59/80 (73.8%) women (25 radiotherapy and 34 chemotherapy). High preoperative serum cancer antigen-125 level (25.1±20.2 vs. 11.5±6.5 IU/mL, p<0.001), open surgery (71.2% vs. 28.6%, p=0.001), myometrial invasion (MI) ≥1/2 (33.9% vs. 0, p=0.002), and lymphovascular space invasion (LVSI; 28.8% vs. 4.8%, p=0.023) were frequent in women who received adjuvant therapy compared to those who did not. However, the histologic type, MI ≥1/2, and LVSI did not differ between women who received adjuvant radiotherapy and those who received chemotherapy. The 5-year progression-free survival (78.9% vs. 80.1%, p>0.999) and overall survival (77.5% vs. 87.8%, p=0.373) rates were similar between the groups. Neither radiotherapy (hazard ratio [HR]=1.810; 95% confidence interval [CI]=0.297-11.027; p=0.520) nor chemotherapy (HR=1.638; 95% CI=0.288-9.321; p=0.578) after surgery was independently associated with disease recurrence. Our findings showed similar survival outcomes for adjuvant radiotherapy and chemotherapy in stage I UPSC and CCC of the endometrium. Further large study with analysis stratified by MI or LVSI is required.